PENEGAKAN OTONOMI PASIEN MELALUI PERSETUJUAN TINDAKAN MEDIS (INFORMED CONSENT) - Felenditi, Dionisius (UNIVERSITAS SAM RATULANGI, 2009)
Abstract: Informed consent is the voluntary consent given by the patient for medical treatment, after he/she has obtained all the necessary information about the possible risks of the treatment. Informed consent is done upon the principle of autonomy, beneficence, and nonmaleficence. This is based on the principle of patient dignity wherein the personal autonomy and integrity of the patient is protected and respected. If the patient is incompetent, the consent will be given by the family, the legal proxy, or the guardian. If the family or the guardian is present but they are also incompetent, then the medical staff themselves must make a decision to determine the appropriate medical treatment in accordance with the patient’s condition. Informed consent is especially needed in extraordinary means. Albeit, for a patient in critical condition or in an emergency wherein the medical treatment must be done immediately as a life-saving procedure, proxy consent is not needed. Key words: informed consent/refusal, autonomy, competence, extraordinary means. Abstrak: Informed consent ialah persetujuan bebas yang diberikan oleh pasien terhadap suatu tindakan medis, setelah ia memperoleh semua informasi yang penting mengenai sifat serta konsekuensi tindakan tersebut. Informed consent dibuat berdasarkan prinsip autonomi, beneficentia dan nonmaleficentia, yang berakar pada martabat manusia di mana otonomi dan integritas pribadi pasien dilindungi dan dihormati. Jika pasien tidak kompeten, maka persetujuan diberikan oleh keluarga atau wali sah. Jika keluarga/wali hadir tetapi tidak kompeten juga, maka tenaga medis harus memutuskan sendiri untuk melakukan tindakan medis tertentu sesuai keadaan pasien. Informed consent terutama dibutuhkan dalam kasus-kasus luar biasa (exraordinary means). Namun untuk pasien kritis atau darurat yang harus segera diambil tindakan medis untuk menyelamatkannya, proxy consent tidak dibutuhkan. Kata-kata kunci : persetujuan/penolakan, otonomi, kompetensi, sarana luar biasa.